Working with patients and providers of healthcare to construct a questionnaire that will provide a valid and reliable measure of dignity and privacy for older patients staying in NHS hospitals. - Duncan, Eleanor (2008)
Background and Aim: Dignity is a high priority on quality improvement agendas following its inclusion in the NHS Plan (DH 2000) and the clinical governance agenda (DH 1998). A focused systematic literature review demonstrated that there are no existing questionnaires that measure the extent to which patientsÃÂÃÂ¢ÃÂÃÂÃÂÃÂ dignity and privacy is promoted in healthcare contexts. The aim of the study was to work with patients and providers of healthcare to construct a questionnaire that would provide a valid and reliable measure of dignity and privacy for patients staying in NHS hospitals.